Development and evaluation of a Cassia tora-based herbal antacid suspension - Shivani; Charit Kumar; Rakesh Redhu; Karan Jangra; Amit Lather (Creative Pharma Assent, 2026)
Background: Synthetic antacids are frequently used to manage gastric hyperacidity; however, their potential for long-term adverse effects has catalyzed significant interest in developing safer herbal-based therapeutic alternatives. Cassia tora, traditionally used for gastrointestinal disorders, contains gastroprotective flavonoids, anthraquinones, and tannins. Methodology: To develop and evaluate a Cassia tora-based herbal antacid suspension, assessing its physicochemical stability, microbial safety, phytochemical profile, and acid-neutralizing capacity against a marketed antacid. A methanolic Cassia tora extract was formulated into a suspension with aluminium hydroxide, magnesium hydroxide, and magnesium trisilicate, using controlled flocculation and a structured vehicle. The evaluations included physicochemical properties (pH, viscosity, redispersibility), microbial safety, phytochemical screening, and a 90-day accelerated stability study (ICH guidelines). The acid-neutralizing capacity (ANC) was determined via back titration and compared to that of the marketed antacid and the control. Results and Discussion: The suspension demonstrated acceptable stability over 90 days, with minimal changes in pH (8.86→8.82) and viscosity (1780→1738 cP), and retained easy redispersibility. The microbial counts remained within the pharmacopeial limits. Phytochemical screening confirmed the presence of flavonoids, tannins, and saponins. The ANC was 1.68 mEq, comparable to that of a marketed antacid (2.15 mEq) and significantly superior to that of the control (0.02 mEq). Conclusion: A stable, efficacious Cassia tora-based herbal antacid suspension was successfully developed, exhibiting physicochemical stability, microbial safety, and an ANC comparable to that of commercial formulations. This supports its potential as a natural adjunct, though further in vivo and clinical studies are needed to confirm therapeutic applicability.